2016
DOI: 10.18632/oncotarget.7310
|View full text |Cite
|
Sign up to set email alerts
|

The E1B19K-deleted oncolytic adenovirus mutant AdΔ19K sensitizes pancreatic cancer cells to drug-induced DNA-damage by down-regulating Claspin and Mre11

Abstract: Adenovirus-mediated sensitization of cancer cells to cytotoxic drugs depends on simultaneous interactions of early viral genes with cell death and survival pathways. It is unclear what cellular factors mediate these interactions in the presence of DNA-damaging drugs. We found that adenovirus prevents Chk1-mediated checkpoint activation through inactivation of Mre11 and downregulation of the pChk1 adaptor-protein, Claspin, in cells with high levels of DNA-damage induced by the cytotoxic drugs gemcitabine and ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 59 publications
1
38
0
Order By: Relevance
“…Our data demonstrate that viral efficacy was retained in the 3D cultures when Ad5-3D-A20T was combined with low doses of gemcitabine. The deletion of the E1B19K gene causes enhancement of gemcitabine-dependent apoptosis, previously demonstrated for AdDD in PDAC cells (6,11,12,14). We propose that the 3D cocultures are suitable model systems for investigating oncolytic virus replication and spread in the presence of the multiple cell types that constitute the tumor microenvironment in patients.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Our data demonstrate that viral efficacy was retained in the 3D cultures when Ad5-3D-A20T was combined with low doses of gemcitabine. The deletion of the E1B19K gene causes enhancement of gemcitabine-dependent apoptosis, previously demonstrated for AdDD in PDAC cells (6,11,12,14). We propose that the 3D cocultures are suitable model systems for investigating oncolytic virus replication and spread in the presence of the multiple cell types that constitute the tumor microenvironment in patients.…”
Section: Discussionmentioning
confidence: 73%
“…S4). We previously demonstrated that both AdDD and AdD19K synergized with low doses of gemcitabine in pancreatic cancer cells in 2D monocultures and in vivo, including Suit-2 models, by enhancing apoptotic death through mitotic aberrations (11,14). We found that the 3D coculture system was a suitable model for screening the efficacy of adenoviral mutants and for confirming compatibility with current therapeutic cytotoxic drugs.…”
Section: Viral Genome Amplification Is Increased With A20fmdv2-expresmentioning
confidence: 93%
See 3 more Smart Citations